42.5k views
5 votes
X - у - 2z = -6
3х + 2y = -25
—4х + у — z = 12

User DoTheEvo
by
4.8k points

1 Answer

7 votes

Answer:

(1) x-y-2z=-6 , (2) 3x+2y=-25 , (3) -4x+y-z=12

Explanation:

Multiply (3) by 2,

-8x + 2y - 2z = 24

subtract above equation from (1)

9x - 3y = -30 --> 3x - y = - 10

subtract above equation from (2)

3y = -15 --> y = -5

Put y value back into (2)

3x + 2(-5) = -25 --> 3x - 10 = -25 --> 3x = -15 --> x = -5

Put x and y values into (3)

-4(-5) + (-5) - z = 12 --> 20 - 5 - z = 12 --> 15 - z = 12 --> z = 3

Hope its right good luck!!

User Elvi
by
5.6k points